Numerical analysis of glulam beams reinforced with CFRP plates - Glišović, Ivan; Pavlović, Marko; Stevanović, Boško; Todorović, Marija (Journal of Civil Engineering and Management, 2017)
This paper presents an analysis of bending behaviour of glued laminated timber (glulam) beams reinforced with carbon fibre reinforced polymer (CFRP) plates, based on finite element numerical modelling. Nonlinear 3-dimensional model was developed and validated by experimental tests carried out on unreinforced beams and beams reinforced with two different reinforcement arrangements. Suitable constitutive relationships for each material were utilised in the model, as well as anisotropic plasticity theory for timber in compression. Adhesive bond between CFRP plate and timber was modelled as a perfect connection. Beam failure in the model was defined by maximum stress criterion. The predicted behaviour of beams has shown good agreement with the experimental results in relation to load-deflection relationship, ultimate load, elastic stiffness and strain profile distribution. The non-linear behaviour of reinforced beams before failure was also achieved in the numerical analysis, confirming the finite element model to be accurate past the linear-elastic range. Experimentally tested reinforced beams usually failed in tensile zone after compressive plasticization of top lamination, which was also simulated in the numerical model. The results proved that the load carrying capacity, stiffness and ductility of glulam beams were successfully increased by addition of CFRP plate at tension side of the section.